Pengelolaan Pembelajaran Akidah Akhlak di MAN Pematangsiantar - Andriyani, Nursuciana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The aim of this research is to find out how learning is managed at MAN Pematangsiantar,whether learning planning, learning implementation, and learning supervision have been carried out and implemented effectively or not. This type of research uses qualitative methods using a descriptive approach where the data collected is not in the form of numbers but interview scripts, field notes and pictures.to obtain accurate data, researchers used data collection methods in the form of observation, interviews and documentation. The research result obtained are as follows:the first is the management of Aqidah Akhlak learning at MAN Pematangsiantar, how is the learning planning carried out by teachers in learning aqidah akhlak.Â  Second, how is the implementation of learning carried out by the teacher, whether it is good and conveyed to the students. Third, how to supervise the learning of the Aqidah akhlak conducted by the teacher during the learning procces, as well as what are the solutions and efforts of the teacher in overcoming the obstacles that exist during the learning process is in progress.